Awareness of Noise Hazards and the Value of Soundscapes in Polish National Parks - BERNAT, Sebastian (Archives of Acoustics, 2013)
The goal of the studies undertaken in Polish national parks was to determine noise threats, examinethe resources, assess the quality of soundscapes and identify the possibilities of their protection. Thequestionnaire method used in the studies made it possible to identify the awareness of noise threats andthe value of soundscapes according to the park service staff. In addition, the semantic differential anddescription methods were used to learn how students assessed the soundscape quality of Polish nationalparks. Finally, avenues of further research on soundscape in environmentally valuable areas were indicated.The research findings indicate that each national park in Poland is characterised by diverse and uniquesoundscapes and is subject to the pressure of road traffic and tourism resulting in noise hazards. Theconservation of the acoustic values of parks is necessary and possible.